PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTY AND REAL ESTATE TBK PERIODE 2017-2019 - Permatasari, Nita (Jurnal Jejama Manajemen Malahayati, 2022)
The purpose of this study was to determine how much influence the implementation of good corporate governance has on financial distress. Data were collected through purposive sampling, with 15 property and real estate companies listed on the Indonesia Stock Exchange 2017-2019. The analytical method used is multiple linear analysis. And hypothesis testing using partial T test, simultaneous F test with a significant level of 5% and the determinant coefficient. The results of this test indicate that the partial hypothesis of Managerial Ownership has a significant effect on the Financial Distress variable while the Board of Directors, Independent Commissioner, Institutional Ownership, and the Audit Committee have no significant effect on the Financial Distress variable. However, based on the simultaneous testing of the board of directors, independent board of commissioners, managerial ownership, institutional ownership, and audit committee together have a significant effect on Financial Distress. The result of the coefficient of determination test (R2) is 0.249. Penelitian yang dilakukan oleh Helena dan Saifi (2018), menyatakan bahwa dewan direksi berpengaruh positif terhadap financial distress